Plateau problem and minimal surfaces: numerical methods and applications - Sapagovas, Mifodijus (Lietuvos matematikos rinkinys, 2023)
This article presents an overview of the results of solving the minimal surface equation by numerical methods. Another research task is the application of minimal surfaces in science, technology, especially architecture. The article is illustrated with examples of the application of minimal surfaces.